Enhancing doxorubicin anticancer activity with a novel polymeric platform photoreleasing nitric oxide. (8th January 2020) - Sodano, Federica; Cavanagh, Robert J.; Pearce, Amanda K.; Lazzarato, Loretta; Rolando, Barbara; Fraix, Aurore; Abelha, Thais F.; Vasey, Catherine E.; Alexander, Cameron; Taresco, Vincenzo; Sortino, Salvatore
Abstract : Combination of Doxorubicin with light-regulated NO release achieved through formulation strategy of tailored polymeric conjugate nanoparticles may open new treatment modalities to improve cancer therapies. Abstract : Combinations of conventional chemotherapeutics with unconventional anticancer agents such as reactive oxygen and nitrogen species may offer treatment benefits for cancer therapies. Here we report a novel polymeric platform combining the delivery of Doxorubicin (DOXO) with the light-regulated release of nitric oxide (NO). An amphiphilic block-copolymer (P1) was designed and synthesized as the drug carrier, with pendant amine groups to attach DOXO via a urea linkage and a NO photodonor (NOPD) activable by visible light. The two grafted-copolymers (P1-DOXO and P1-NOPD) self-assembled via solvent displacement methods into nanoparticles (NPs), containing both therapeutic components (NP1) and, for comparison, the individual NOPD (NP2) and DOXO (NP3). All the NPs were fully characterized in terms of physicochemical, photochemical and photophysical properties. These experiments demonstrated that integration of the NOPD within the polymeric scaffold enhanced the NO photoreleasing efficiency when compared with the free NOPD, and that the proximity to DOXO on the polymer chains did not significantly affect the enhanced photochemical performance. Internalization of the NPs into lung, intestine, and skin cancer cell lines was investigated after co-formulation with Cy5 fluorescent tagged polymers, and cytotoxicity of the NPs against the same panel of cell lines was assessed under dark and light conditions. The overall results demonstrate effective cell internalization of the NPs and a notable enhancement in killing activity of the dual-action therapeutic NP1 when compared with NP2, NP3 and the free DOXO, respectively. This suggests that the combination of DOXO with photoregulated NO release, achieved through the mixed formulation strategy of tailored polymer conjugate NPs, may open new treatment modalities based on the use of NO to improve cancer therapies.